Effect of adding different levels of oil mill waste water to the subsurface soil layer on some physical and hydrodinamical properties of this layer during the micanical dismantling - بدور رشا; جهاد ابراهيم; ربيع زينة (Latakia University Journal -Biological Sciences Series, 2023)
Through the study conducted on silty clay soil on the effect of adding different levels of oil mill waste water (OMWW) to the subsurface soil layer on some physical and hydrodynamical properties of this layer during mechanical dismantling, it was found that the bulk density decreased significantly after mechanical dismantling by 0.14 g/cm3 compared to the control, and it decreased by 0.2 g/cm3 when adding the first level of oil mill waste water (2 liters/m2), and 0.24g/cm3 when adding the second level of oil mill waste water (4 liters/m2) compared to the control. The total porosity increased after mechanical dismantling by 1.34%, and by 7.46% when adding the first level of (OMWW), and increased by 8.82% when adding the second level of (OMWW) compared to the control. The air pore size greater than 50 micron increased significantly after mechanical dismantling from 8.1% to 15.4%, and reached 14.43% when adding the first level of (OMWW) , and 18.22% when adding the second level of (OMWW) compared to the control. The volume of air pores greater than 10 micron increased significantly after mechanical dismantling from 9.9% to 16.34%, and it became 18.02% at the first addition level, and 18.98% at the second application level compared to the control. The pore size between 0.2 and 10 micron - responsible for the available water - increased after mechanical dismantling by 1.42%, which is an insignificant increase, while it increased significantly by 2.7% when adding the first level of (OMWW) , and by 3.7% when adding the second level of (OMWW) compared to the control. The size of the small pores - less than 0.2 micron - decreased significantly when mechanical dismantling from 25.2% to 22.68%, and decreased significantly to 21.84% when adding the first level of (OMWW), and to 21.34% when adding the second level of (OMWW) compared to the control. The saturated hydraulic conductivity coefficient increased significantly by 12.7 times with mechanical disassembly, and 15.8 times when adding 2 liters/m2 of (OMWW), and 23.3 times when adding 4 liters/m2 of (OMWW) compared to the control. The hydrodynamic constants of the soil increased with mechanical disassembly compared to the control. With an increase in the percentage of (OMWW) addition, it increased from 0.001345 in the control treatment to 0.0634 for the constant a, and from -11.9836 in the control treatment to -8.149 for the constant b.